DIRECTIONS FOR ENSURING ECONOMIC SECURITY ON THE BASIS OF INTERNATIONAL EXPERIENCE - Avazov, Nuriddin (International Journal of Business, Law, and Education, 2020)
This article analyzes the directions of economic security. In order to ensure economic security, economic security indicators must be within the established limits. The analysis was based on international experience. In international experience, the two largest economies in the world, the United States and the Russian Federation, have considered models for economic security. Based on the analysis, a modern approach to economic security has been proposed.